2021
DOI: 10.3389/fvets.2021.693082
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pig Tuberculosis in Argentina

Abstract: Bovine tuberculosis (bTB) is a disease caused mainly by the Mycobacterium bovis and that is endemic to livestock populations in most Latin American countries. Traditionally, bTB control programs are costly and targeted to cattle, largely disregarding other species such as swine and wildlife. According to official services, in Argentina disease prevalence in pigs is comparable to that observed in cattle, suggesting the need for efficient control programs to manage the disease in both species. Additionally, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The presence of NTM in free-ranging animals that share their environment with livestock highlights the need to differentiate mycobacteria species, because of the potential interference in diagnostic tests, to control mTB ( 4 , 68 , 70 ). In Argentina, there is a particular scenario where extensive livestock farming is the most frequent strategy, allowing domestic and wild animals to interact in the same environment, increasing the likelihood of disease transmission between them, compared to more confined and intensive farming scenarios ( 56 , 69 ). The adverse consequences associated with the introduction of livestock into habitats occupied by native fauna have been extensively documented, primarily due to the spread of infectious and parasitic diseases ( 71 78 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of NTM in free-ranging animals that share their environment with livestock highlights the need to differentiate mycobacteria species, because of the potential interference in diagnostic tests, to control mTB ( 4 , 68 , 70 ). In Argentina, there is a particular scenario where extensive livestock farming is the most frequent strategy, allowing domestic and wild animals to interact in the same environment, increasing the likelihood of disease transmission between them, compared to more confined and intensive farming scenarios ( 56 , 69 ). The adverse consequences associated with the introduction of livestock into habitats occupied by native fauna have been extensively documented, primarily due to the spread of infectious and parasitic diseases ( 71 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…These Mycobacteria can be isolated from soil, water and occasionally have been associated with disease in animals and humans (3,(49)(50)(51)(52)(53)(54)(55). M. avium has been isolated from several wild species (4) and MAH has already been reported in wild and domestic animals in Argentina (56). M.intrcellulare has been reported causing disease in a capybara subjected to stressful conditions and causing lesions similar to other pathogenic Mycobacteria (5).…”
Section: Discussionmentioning
confidence: 99%
“…We found particularly relevant results regarding cattle contact with wild MTC susceptible hosts and MTC host species richness. Sheep are part of the MTC maintenance communities in speci c circumstances (Muñoz-Mendoza et al 2016;Pozo et al 2024); and, in some regions, TB prevalence in pigs is comparable to the one observed in cattle(Barandiaran et al 2021). However, we found an absence of evidence of a statistically signi cant effect of the numbers of both species, when considered on their own, with respect to TB-status.…”
mentioning
confidence: 99%